2015
DOI: 10.1097/ftd.0000000000000139
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the New RapidFire System for Therapeutic Monitoring of Immunosuppressants

Abstract: The RapidFire-MS/MS system provided convincing results measuring patient samples and quality control materials. Together with a high throughput and a high robustness, it could represent an alternative to LC-MS/MS instruments in therapeutic drug monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…The between-run CV was 1.8%-13.0% for cyclosporine A, tacrolimus, sirolimus, and everolimus. In another study, the analytical column was replaced with a solid-phase extraction cartridge; thus completely avoiding LC separation [49]. This lowered the analytical run time to 13 s. The assay was compared to an LC-MS/ MS method, showing 0.964 as the lowest Pearson correlation coefficient with Deming regression and 2.9% as the largest mean concentration difference.…”
Section: Throughput Improvement For Lc-ms/ms Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The between-run CV was 1.8%-13.0% for cyclosporine A, tacrolimus, sirolimus, and everolimus. In another study, the analytical column was replaced with a solid-phase extraction cartridge; thus completely avoiding LC separation [49]. This lowered the analytical run time to 13 s. The assay was compared to an LC-MS/ MS method, showing 0.964 as the lowest Pearson correlation coefficient with Deming regression and 2.9% as the largest mean concentration difference.…”
Section: Throughput Improvement For Lc-ms/ms Methodsmentioning
confidence: 99%
“…Lastly, a fourth group found that differences in hematocrit (20% to 45%), spotted blood volume (25,35,50,75, and 100 μL), and punch location did not affect immunosuppressant quantitation [39]. [46,47] Online solid phase extraction (analytical run time of 1 min) [48] No LC separation (analytical run time of 13 s) [49] Liquid handler [50] Commercialization/ Standardization 7-Lab tacrolimus unification [52] 3-Lab cyclosporine A, tacrolimus, and sirolimus unification [53] Much of these DBS validation studies involve the deposition of venous blood from a collection tube onto the paper. Two recent studies evaluated capillary blood from a finger stick.…”
Section: Non-traditional Sample Types For Lc-ms/ms Analysismentioning
confidence: 98%
“…Several techniques have been developed to increase the throughput of LC–MS/MS. Among them, UPLC is one of the most commonly used techniques . UPLC increases the throughput by shortening the LC run time while retaining the resolution by using smaller‐diameter separation media and very high pressure.…”
Section: Chromatography Methodsmentioning
confidence: 99%
“…Among them, UPLC is one of the most commonly used techniques. [33][34][35][36][37][38] Furthermore, sample preparation was simple, and this method could In addition to the blood samples for the TDM of ISDs, other potential and convenient specimens, including saliva, hair, and ocular fluids, have also been explored when whole-blood levels are within the therapeutic range. [47][48][49][50][51] Belostotsky et al 47…”
Section: Throughput Improvementmentioning
confidence: 99%
See 1 more Smart Citation